2017
DOI: 10.3390/met7110461
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Powder Metallurgy Processed Pure Magnesium Materials for Biomedical Applications

Abstract: Magnesium with its mechanical properties and nontoxicity is predetermined as a material for biomedical applications; however, its high reactivity is a limiting factor for its usage. Powder metallurgy is one of the promising methods for the enhancement of material mechanical properties and, due to the introduced plastic deformation, can also have a positive influence on corrosion resistance. Pure magnesium samples were prepared via powder metallurgy. Compacting pressures from 100 MPa to 500 MPa were used for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Moreover, in the presence of Cl − ions in the solution, this layer is being constantly disrupted. As a result, MgCl 2 soluble in the water solution (corrosive environment) is formed (Equation (4)) [3,21,31]. The formation of MgCl 2 disrupts the compactness of protective Mg(OH) 2 layer.…”
Section: Electrochemical Polarization Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in the presence of Cl − ions in the solution, this layer is being constantly disrupted. As a result, MgCl 2 soluble in the water solution (corrosive environment) is formed (Equation (4)) [3,21,31]. The formation of MgCl 2 disrupts the compactness of protective Mg(OH) 2 layer.…”
Section: Electrochemical Polarization Measurementsmentioning
confidence: 99%
“…This model describes the behavior of uncoated AZ91 alloy exhibited in 0.1 M NaCl solution for 5 min. The model corresponds to the formation of a thin layer of Mg(OH) 2 on the metallic surface of AZ91 alloy [31]. However, formed Mg(OH) 2 layer is not completely uniform due to its porous nature and is also damaged by cracks, and so the metallic surface of AZ91 alloy was in contact with the corrosive environment [3,21].…”
Section: Electrochemical Impedance Spectroscopy Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, ground samples of AZ61 in HBSS+ solution displayed R p values which are higher than those obtained with polished samples. The effect of processing parameters on mechanical properties and corrosion degradation of pure Mg in terms of powder metallurgy technology was evaluated by Matej Brezina et al [9]. They found that cold-compacted samples were quite brittle, with reduced strength (up to 50 MPa) and accelerated corrosion degradation, as compared to hot-pressed samples that yielded much higher strength (up to 250 MPa) and significantly improved corrosion resistance.…”
Section: Contributionsmentioning
confidence: 99%